Exploring the Relationship between Perfectionism and Pain in Patients with Temporomandibular Disorders: A Cross-Sectional Study - Xin Xiong; Shi-Yong Zhang; Jing Zhang; Nan Jiang; Li-Ming Zhang; Hao-Lun Yang; Yuan Yue (International Journal of Clinical Practice)
Objectives. The purpose of this cross-sectional study was to examine the relationship between perfectionism and pain in patients with temporomandibular disorders (TMDs). Methods. A total of 345 TMD patients were included. A questionnaire consisting of questions of demographic information, the 15-item short form of the Hewitt and Flett Multidimensional Perfectionism Scale, and the Patient Health Questionnaire-4 (PHQ-4) was distributed. According to the diagnostic criteria for TMDs, patients were categorized as pain-related (PT) and non-pain-related (NPT) groups, whereas PT patients were further divided into patients with pain-related TMDs only (OPT) and patients with combined pain-related and intra-articular TMDs (CPT). Data were analyzed using the chi-square test, Spearman’s correlation, and logistic regression analysis with the significance level set at p<0.05. Results. There were 68 patients in the NPT group, 80 in the OPT group, and 197 in the CPT group. PT patients had significantly higher perfectionism scores (63.58 ± 13.63) than NPT patients (56.32 ± 12.95, p<0.001). The PHQ-4 score in the PT group was also higher. After adjusting the PHQ-4 scores, perfectionism scores of the PT group were 6.11 points higher than those in the NPT group (p<0.001). There were no statistical differences in all parameters of OPT and CPT groups (p>0.05). Perfectionism in total, other-oriented perfectionism (OOP), and socially prescribed perfectionism (SPP) showed significant but weak correlations with PHQ-4 scores (p<0.001), while self-oriented perfectionism (SOP) was also significantly but very weakly correlated with PHQ-4 scores (p<0.05). Conclusions. Pain-related TMD patients exhibited higher perfectionism scores than NPT patients, and neither their perfectionism nor pain scores were correlated with intra-articular diseases of TMJ. OOP and SOP presented weak correlations with psychological distress in TMD patients. It is suggested that pain-related TMD patients could be screened for perfectionism and perfectionism could be considered when proposing psychological treatment strategies to PT patients.